Drivers of Patient Costs in Accessing HIV/AIDS Services in Tanzania. (16th May 2018) - Mnzava, Thomas; Mmari, Eunice; Berruti, Andres
Background: Patient costs pose a challenge in accessing antiretroviral therapy for people living with HIV in sub-Saharan Africa. The study aimed at identifying drivers for out-of-pocket (OOP) costs in Tanzania. Methods: In 2009, 500 adult patients who attended 10 HIV clinics across 7 regions of Tanzania were asked about time and resources consumed to access HIV services. Bivariate and multivariate median regression models were used to determine the main drivers for OOP costs. Results: Male and female patients have a median OOP costs of 40.37 and 28.01 per year, respectively ( P = .01). Males spend significantly more on travel (26.51) than females (19.68; P = .02). Living in rural areas and poor social economic status (SES) are associated with greater OOP costs ( P = .001) for both sexes. Conclusion: Poor SES and rural residence are main drivers of OOP costs. Patients are less likely to seek health care unless they are in dire need, leading to expensive services.